2010
DOI: 10.1128/jcm.01996-09
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus DNA Detection in Menstrual Blood from Patients with Cervical Intraepithelial Neoplasia and Condyloma Acuminatum

Abstract: The Papanicolaou test generates pain and embarrassment, and cytology screening has limited sensitivity for detection of cervical neoplasia. These factors urge the use of another screening test that can overcome these limitations. We explore a completely noninvasive method using detection of human papillomavirus (HPV) DNA in women's menstrual blood (MB). The participants were divided into 3 cohorts: (i) 235 patients with cervical intraepithelial neoplasia 3 (CIN 3) (n ‫؍‬ 48), CIN 2 (n ‫؍‬ 60), CIN 1 (n ‫؍‬ 58)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 20 publications
(17 reference statements)
0
29
0
Order By: Relevance
“…Additionally, in a study involving a general population of patients who visited clinics for routine examinations, the HPV tests using MB and clinician‐performed cervical HPV tests had 97.8% agreement for the detection of HPVs . Although previous investigators have reported a high agreement rate for detecting HR‐HPVs from cervical and MB samples, they did not target HR‐HPVs or the studies were performed in a case–control setting . In contrast to previous studies, we were able to provide data regarding the detection of HR‐HPV in MB, especially in patients with CIN 2, 3 and cancer, according to MCD, in a prospective cohort setting (Table and ).…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Additionally, in a study involving a general population of patients who visited clinics for routine examinations, the HPV tests using MB and clinician‐performed cervical HPV tests had 97.8% agreement for the detection of HPVs . Although previous investigators have reported a high agreement rate for detecting HR‐HPVs from cervical and MB samples, they did not target HR‐HPVs or the studies were performed in a case–control setting . In contrast to previous studies, we were able to provide data regarding the detection of HR‐HPV in MB, especially in patients with CIN 2, 3 and cancer, according to MCD, in a prospective cohort setting (Table and ).…”
Section: Discussionmentioning
confidence: 55%
“…According to the analysis of MB collected from the sanitary pads, MB HR‐HPV DNA was detected in 89.8% of HPV DNA‐positive women with CIN 2 and CIN 3 and 26.7% of HPV DNA‐positive women with CIN 1 or condyloma acuminatum . Additionally, in a study involving a general population of patients who visited clinics for routine examinations, the HPV tests using MB and clinician‐performed cervical HPV tests had 97.8% agreement for the detection of HPVs .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations